Integration of inherited sterility and inoculative releases of a miridae predator for the control of the tomato leaf miner, Tuta absoluta - Candas, Lucas (2024)
Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) is one of the most devastating pests of tomato crops worldwide. Tupiocoris cucurbitaceus Spinola (Hemiptera: Miridae) is a predator that can complete its life cycle by preying only on T. absoluta eggs from irradiated parental males or untreated parents. The Inherited Sterility technique (IS) is an environmentally friendly option to control lepidopteran pests whose efficiency is improved when combined with other compatible methods, such as biological control (BC). The aim of this study is to evaluate the effect of integrating T. cucurbitaceus with the IS technique for the suppression of T. absoluta population. Four treatments were carried out in cages in a greenhouse: T1, where untreated T. absoluta adults were released; T2, consisting of the release of irradiated T. absoluta adults in an over-flooding ratio of 15:1 (irradiated:untreated adults); T3, consisting of the release of couples of T. cucurbitaceus; and T4, consisting of the combination of T2 and T3 (IS-BC combination). The number of T. absoluta eggs and larvae in each treatment and the number of T. cucurbitaceus nymphs and adults in T3 and T4 were counted twice a week during three generations of T. absoluta. In all the larval population peaks, the number of individuals was higher in T1 than in the other treatments. The highest population suppression was obtained in T4 compared to the other treatments. These results show that combining T. cucurbitaceus with the IS technique is a useful approach to control the T. absoluta population.